CuIn / BP catalyst for preparing synthesis gas with accurate and controllable proportion through electrocatalytic CO2 reduction as well as preparation method and application of CuIn / BP catalyst

By using CuIn/BP catalyst to electrocatalyze CO2 reduction in aqueous solution, the problem of difficulty in adjusting the H2/CO ratio in the prior art is solved, and the precise control and good stability of the synthesis gas ratio is achieved, which is suitable for industrial applications.

CN119877022APending Publication Date: 2025-04-25HENAN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510325958.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art has difficulty adjusting the H2/CO ratio and bringing it to a specific value within a wide range of applications, especially when obtaining any proportion of synthesis gas.

Method used

CuIn/BP catalyst is used, which electrocatalyzes carbon dioxide reduction in aqueous solution, and uses the unique adsorption characteristics of BP and the active site of CuIn to achieve precise regulation of the H2/CO ratio. The added amount of BP is linearly related to the ratio of synthesis gas. Different proportions of synthesis gas can be obtained by simply changing the added amount of BP.

Benefits of technology

The electrocatalytic CO2 reduction in aqueous solution is achieved to produce a synthesis gas with accurate and controllable proportions. The catalyst has good stability, is suitable for industrial applications, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a CuIn / BP catalyst for preparing synthesis gas with an accurate and controllable proportion by electrocatalytic reduction of CO2, which adopts a simple sodium borohydride NaBH4 one-step co-reduction method to co-reduce a mixture of a Cu precursor, an In precursor and a black phosphorus crystal BP into a CuIn / BP particle electrocatalyst. When the composite material is applied to electrocatalytic reduction of carbon dioxide (CO2), CO2 can be reduced into synthesis gas with an accurate and adjustable proportion in a water-containing electrolyte, and excellent catalytic activity is shown. The synthesis gas with any H2 / CO molar ratio can be obtained through electrocatalytic reduction of CO2 only by changing the addition amount of BP in the catalyst synthesis process, and the requirements of downstream industrial application are met. The preparation method is simple and easy to obtain, and has a good application prospect in the field of electrocatalytic reduction of CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electric energy catalytic conversion, and specifically relates to a CuIn / BP catalyst for electrocatalytic reduction of carbon dioxide in an aqueous solution to produce synthesis gas with a precisely controllable and adjustable ratio, as well as a preparation method and application thereof. Background Art

[0002] Since the Industrial Revolution, the massive consumption of fossil fuels has led to a continuous increase in the concentration of carbon dioxide (CO2) in the atmosphere, causing serious climate problems. Electrochemical reduction of CO2 driven by renewable energy electricity is considered to be a viable solution to both reduce CO2 emissions and alleviate dependence on traditional fossil resources. Among the various reduction products, syngas (a mixture of hydrogen H2 and carbon monoxide CO) has attracted widespread attention because syngas is an important raw material for the Fischer-Tropsch process, and the final product of the Fischer-Tropsch process depends largely on the H2 / CO ratio. To date, many researchers have been working hard to improve the activity and selectivity of electrocatalysts to achieve a controllable H2 / CO ratio.

[0003] The hydrogen evolution reaction (HER) is an inevitable competitive reaction of the carbon dioxide reduction reaction (CO2RR) in aqueous solution, and inhibiting HER is a common way to adjust the H2 / CO ratio. At present, single metal catalysts such as Au, Pd, and Ag are often used as catalysts for CO2RR to generate CO, with excellent CO production selectivity. However, it is difficult to produce an ideal syngas with a desired H2 / CO ratio based on single metal electrocatalysts. The ability of single metal centers to simultaneously inhibit HER and activate CO2RR is limited. Therefore, bimetallic electrocatalysts are developed by introducing another metal active site. Two different active sites are used to promote HER and CO2RR respectively to adjust the H2 / CO ratio. Alternatively, different metal active sites are used to adjust the generation of CO by regulating different electron transfer processes in CO2RR (i.e., adsorption of *COOH and desorption of *CO), thereby achieving the ultimate goal of controlling the H2 / CO ratio. Although many advances have been made, it is still not easy to adjust the H2 / CO ratio and reach a specific value in a wide range of applications. More specifically, there are almost no feasible and effective strategies to obtain syngas with any ratio.

[0004] In the past few decades, most studies have only tuned the catalytic behavior by changing the metal content, with the goal of controlling the H2 / CO ratio. In addition to composition, microstructure, phase, and exposed crystal planes also have a great influence on the activity and selectivity of the catalyst. However, compared with composition regulation, the synthesis and characterization of bimetallic catalysts with different element arrangements are more difficult. Therefore, it is necessary to develop a facile method to prepare bimetallic electrocatalysts that produce tunable H2 / CO ratio synthesis gas. It is reported that there is currently little research to achieve the above goal by introducing other materials. Surprisingly, black phosphorus (BP) nanosheets have great potential in the process of generating H2 from water splitting reaction due to their weak adsorption energy for H* and strong adsorption energy for intermediates containing O*. In addition, the exposed lone pairs of electrons in BP have high adsorption energy for metals, oxygen, and hydrogen, which provides an opportunity to combine with other bimetallic catalysts for CO2RR to achieve precisely customized synthesis gas. In view of this, the present invention is proposed. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a novel CuIn / BP electrocatalyst for electrocatalytic reduction of carbon dioxide in aqueous solution to produce synthesis gas with precise controllable and adjustable ratio. The catalyst has excellent performance of electrocatalytic reduction of CO2 to produce synthesis gas, wherein the amount of BP added during CuIn / BP synthesis is linearly related to the ratio of synthesis gas in the reduction product, and any specific ratio of synthesis gas can be obtained by simply changing the amount of BP added, meeting the needs of downstream industrial applications.

[0006] The present invention also provides a preparation method and application of the CuIn / BP electrocatalyst for electrocatalytic CO2 reduction to produce synthesis gas in a precisely controllable and adjustable ratio.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a CuIn / BP catalyst for electrocatalytic CO2 reduction to produce syngas with a precisely controlled ratio, comprising the following steps: 1) exfoliating black phosphorus (BP) crystals to form black phosphorus monolayer nanosheets; dispersing the black phosphorus monolayer nanosheets in DMF to form a precursor solution A; 2) Dispersing metal copper salt and metal indium salt in deionized water to form precursor solution B; 3) Disperse NaBH4 in deionized water to form solution C; 4) After mixing precursor solution A and precursor solution B at room temperature, add solution C, wait for complete precipitation, and separate the solid and liquid to obtain the CuIn / BP catalyst.

[0008] Specifically, in step 1), the commercial black phosphorus crystals purchased can be exfoliated in a N,N-dimethylformamide (DMF) solution containing tetrabutylammonium hexafluorophosphate (TBAP) using a DC power supply to apply voltage to form a black phosphorus monolayer nanosheet, and the applied voltage is -10~-14 V.

[0009] As a preferred technical solution, further, in step 1), 2 g of black phosphorus crystals can be added to 30-50 mL of N,N-dimethylformamide solution containing 1-3 g of tetrabutylammonium hexafluorophosphate.

[0010] Specifically, in step 2), the metal copper salt may be copper nitrate trihydrate (Cu(NO3)2·3H2O), and the metal indium salt may be indium nitrate hydrate (In(NO3)3·xH2O); the molar ratio of the metal copper salt to the metal indium salt is 3-5:1, preferably 4:1. For example, in the precursor solution B, the amount of the metal copper salt added may be 1.6 mmol, and the amount of the metal indium salt added may be 0.4 mmol, and the corresponding amount of deionized water added is 20 mL.

[0011] Furthermore, the molar ratio of the black phosphorus monolayer nanosheet, the sum of the molar amounts of the metal copper salt and the metal indium salt, and NaBH4 is 0.001-0.1:2:3. For example, in the precursor solution A, the amount of black phosphorus monolayer nanosheet added can be 50 ~ 1000 μg; the amount of sodium borohydride added in solution C can be 3 mmol, and the corresponding amount of deionized water added is 2 mL. Taking the addition amount of black phosphorus monolayer nanosheet as 350 μg as an example, the molar percentage of BP in the catalyst compared to the sum of the molar amounts of the metal copper salt and the metal indium salt is 0.56%, recorded as Cu4In1 / BP-56, and so on.

[0012] The present invention provides a CuIn / BP catalyst prepared by the above preparation method.

[0013] The present invention also provides the use of the above-mentioned CuIn / BP catalyst in the electrocatalytic reduction of CO2 to produce synthesis gas with precise and controllable proportions. The CuIn / BP catalyst can be made into a working electrode, that is, the CuIn / BP catalyst can electrocatalytically reduce CO2 and can precisely control the reduction of CO2 to any proportion of synthesis gas.

[0014] Specifically, in the above application, the CuIn / BP catalyst can be dispersed in a volatile solvent, and a Nafion solution is added as a binder, and ultrasonic dispersion is performed to obtain a uniform electrode dispersion; the electrode dispersion is coated on carbon paper and dried at room temperature to obtain a working electrode; and constant voltage electrolysis is performed in a closed three-electrode system.

[0015] Furthermore, the volatile solvent is isopropanol; the volume ratio of the volatile solvent to the Nafion solution is 22-26:1, the mass concentration of the Nafion solution is 4-6%; the concentration of the CuIn / BP catalyst in the electrode dispersion is 8-12 mg / mL -1 .

[0016] Further preferably, the three-electrode system uses a saturated calomel electrode as a reference electrode and a platinum mesh electrode as a counter electrode, and performs constant voltage electrolysis in a 0.5 M KHCO3 aqueous solution, and the voltage used for constant voltage electrolysis is -0.5 V to -0.9 V (vs. RHE). The electrolytic cell adopts an H-type electrolytic cell, with the working electrode and the reference electrode at one end and the counter electrode at the other end.

[0017] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1) This invention proposes for the first time that CuIn bimetallic salt and BP monolayer nanosheets are used as precursors, and a simple one-step NaBH4 co-reduction method is used to prepare CuIn / BP catalysts, which are applied to the electrocatalytic reduction of CO2 to produce syngas with a precisely adjustable ratio. The application of two-dimensional nanosheet BP containing lone pairs of electrons in the electrocatalytic reduction of CO2 provides a new idea for the preparation of electrocatalytic reduction of CO2 catalysts.

[0018] 2) The catalyst of the present invention has excellent performance in electrocatalytic reduction of CO2 to produce synthesis gas. The synthesized CuIn / BP catalyst can obtain synthesis gas of different proportions simply by changing the amount of BP added during the synthesis process. The amount of BP added and the proportion of synthesis gas are similarly linearly related, which can meet the needs of different downstream industrial applications.

[0019] 3) During the constant potential electrolysis process of -0.6 V (vs. RHE) and 18 h for the Cu4In1 / BP-63 catalyst of the present invention, the proportion of synthesis gas and the current density did not decrease significantly, and the electrocatalytic reduction of CO2 could maintain the synthesis gas with a H2 / CO ratio close to 2:1, with good stability.

[0020] 4) The catalyst synthesis method is simple and easy. The catalyst is obtained by one-step reduction and does not require further treatment. It has the potential to be applied to industrial production and has good application prospects in the field of electrocatalytic reduction of carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the synthesis of the CuIn / BP-m catalyst of the present invention.

[0022] Figure 2TEM (ab), HRTEM (cd) of the catalysts prepared in Example 2 (Cu4In1 / BP-56) and Example 3 (Cu4In1) of the present invention, and EDS Mapping image (e) of the catalyst prepared in Example 2 (Cu4In1 / BP-56); Figure 3 The XRD patterns (a) of the catalysts prepared in Example 2 (Cu4In1 / BP-56) and Example 3 (Cu4In1) of the present invention and the XPS pattern of the catalyst (Cu4In1 / BP-56) prepared in Example 2 are shown in Figure 1. (b) is the full XPS spectrum of Cu4In1 / BP-56, (c) is the Cu 2p XPS pattern of Cu4In1 / BP-56, (d) is the In 3d XPS pattern of Cu4In1 / BP-56, (e) is the P 2p XPS pattern of Cu4In1 / BP-56, and (f) is the Cu LMM Auger XPS pattern of Cu4In1 / BP-56. Figure 4 The present invention is Example 3 (Cu4In1), Example 4 (Cu n XPS graphs of the catalysts prepared in Example 1), Example 5 (Cu) and Example 6 (In): (a) Cu 2p XPS graph, (b) In 3d XPS graph; Figure 5 The present invention is Example 3 (Cu4In1), Example 4 (Cu n In1) and Example 5 (Cu) catalytic reduction of carbon dioxide Faraday efficiency diagram: (a) CO2 reduction gas production Faraday efficiency of Cu sample and (b) -0.5 V vs. RHE, (c) -0.6 V vs. RHE, (d) -0.7 V vs. RHE, (e) -0.8 V vs. RHE and (f) -0.9 V vs. RHE, Cu n Faradaic efficiency of CO2 reduction to gas production of In1; Figure 6 The catalyst (Cu4In1 / BP-m) prepared in Example 1 of the present invention is a Faraday efficiency and current density diagram of CO2 reduction to produce synthesis gas at -0.6 V vs. RHE at different BP contents (a), and a linear fitting curve of BP content and H2 / CO ratio in synthesis gas (b).

[0023] Figure 7The catalyst (Cu4In1 / BP-m) prepared in Example 1 of the present invention is the Faraday efficiency and current density diagram of CO2 reduction to produce synthesis gas at -0.5 V vs. RHE and -0.9 V vs. RHE at different BP contents (a, c), and the linear fitting curve of BP content and H2 / CO ratio in synthesis gas (b, d).

[0024] Figure 8 The catalyst (Cu4In1 / BP-m) prepared by the present invention was tested for verification of the BP content by inversely estimating the BP content through a linear fitting curve: the H2 / CO ratio was 1:2, corresponding to a BP content of 0.25% (a), 1:1 corresponding to a BP content of 0.38% (b) and 2:1 corresponding to a BP content of 0.63% (c), and the verification was performed 5 times respectively; Fig. 9 This is a stability test diagram of the catalyst Cu4In1 / BP-63 (corresponding to a H2 / CO ratio of 2:1) prepared in the present invention; Fig.10 This is an XPS graph of the catalyst Cu4In1 / BP-63 (corresponding to a H2 / CO ratio of 2:1) prepared in the present invention, wherein the XPS characterizations before and after the CO2 electrocatalytic reduction reaction were tested respectively: (a) Cu2p XPS graph of the catalyst before and after the CO2 electrocatalytic reduction reaction, (b) In 3d XPS graph of the catalyst before and after the CO2 electrocatalytic reduction reaction, and (c) P 2p XPS graph of the catalyst before and after the CO2 electrocatalytic reduction reaction. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0026] In the following examples, all the raw materials used are directly available from common commercial products. For example, commercial black phosphorus crystals (>99.998%) were purchased from Hefei Keliao New Material Technology Co., Ltd.; Nafion solution (Nafion perfluorosulfonic acid resin, 5% solution, containing 45% water, 48±3% isopropanol, <4% ethanol) was purchased from Suzhou Shengernuo Technology Co., Ltd.; isopropanol was purchased from Shanghai MacLean Co., Ltd.

[0027] Room temperature refers to 25±5°C.

[0028] Example 1 Preparation of CuIn / BP-m electrocatalyst Preparation method of CuIn / BP catalyst for electrocatalytic CO2 reduction to produce syngas with precise and controllable ratio (synthetic route as shown in Figure 1 ), which comprises the following steps: 1) Weigh 2 g of TBAP and add it to 40 mL of DMF, then add 2 g of commercial black phosphorus crystals, use a DC power supply, clamp the black phosphorus crystals with an electrode clamp as the positive electrode, use a nickel mesh as the negative electrode, and continue to peel for 30 to 45 minutes at a voltage of -12 V to form a black phosphorus monolayer nanosheet. Disperse the black phosphorus monolayer nanosheet in DMF, keep the concentration of the black phosphorus monolayer nanosheet at 5 mg / ml, and form a precursor solution A; 2) Weigh 1.6 mmol Cu(NO3)2·3H2O and 0.4 mmol In(NO3)3·xH2O and add them to 20 mL deionized water, mix and stir to form precursor solution B; 3) Weigh 3 mmol NaBH4 and dissolve it in 2 mL deionized water to form precursor solution C; 4) A certain amount (30, 50, 90, 110, 120, 140 μL) of precursor solution A was taken and added to precursor solution B. After stirring for 5 minutes, the precursor solution C was slowly added dropwise. Wait for about 10 minutes until complete precipitation. Centrifuge at 8000 rpm to obtain a black solid mixture CuIn / BP-m.

[0029] Example 2 Preparation of Cu4In1 / BP-56 electrocatalyst The specific experimental process is similar to that of Example 1, except that the volume of the precursor solution A added in step 4) is changed to 70 μL.

[0030] According to the percentage value of the molar amount of black phosphorus (BP) to the molar amount of Cu4In1, for example, if the volume of precursor solution A added is 70 μL, that is, the mass of BP added is 350 μg, the molar amount of BP added is 0.0113 mmol. Since the total molar amount of Cu4In1 is 2 mmol, the molar percentage of BP / Cu4In1 is 0.56%, and it is named Cu4In1 / BP-56.

[0031] Example 3 Preparation of Cu4In1 electrocatalyst The specific experimental process refers to Example 1, with the only difference being that in step 4), no precursor solution A is added to obtain a Cu4In1 electrocatalyst.

[0032] Example 4 Cu n Preparation of In1 electrocatalyst The specific experimental process is as in Example 1, except that: in step 2), Cu(NO3)2·3H2O and In(NO3)3·xH2O are added in a molar ratio of n:1 (n=1, 2, 8, 16) with a total molar amount of 2 mmol, and the precursor solution A is not added in step 4). b The In1 catalysts are denoted as Cu1In1, Cu2In1, Cu8In1 and Cu 16 In1.

[0033] Example 5 Preparation of Cu electrocatalyst The specific experimental process refers to Example 1, except that only 2 mmol Cu(NO3)2·3H2O is added in step 2) and the precursor solution A is not added in step 4) to obtain a Cu electrocatalyst.

[0034] Example 6 Preparation of In electrocatalyst The specific experimental process refers to Example 1, except that only 2 mmol In(NO3)3·xH2O is added in step 2) and the precursor solution A is not added in step 4) to obtain an In electrocatalyst.

[0035] Example 7 Accurately weigh 5 mg of the catalyst Cu4In1 / BP-m synthesized in Example 2, disperse it in 480 uL of volatile solvent isopropanol, then add 20 uL of Nafion solution (Nafion perfluorinated resin from Shanghai Dibai Biotechnology Co., Ltd., 5% solution, containing 45% water, 48±3% isopropanol, <4% ethanol), and ultrasonically disperse for 30 min to obtain a uniform electrode dispersion. Take 200 uL of the above electrode dispersion and drop it on a 0.5×1 cm 2 The working electrode was prepared by completely drying the carbon paper (HCP020P, from HESEN) at room temperature.

[0036] Example 8 Accurately weigh 5 mg of the catalyst Cu4In1 synthesized in Example 3 and the catalyst Cu synthesized in Example 4 respectively. n In1 was dispersed in 480 uL of volatile solvent isopropanol, and then 20 uL of Nafion solution (Nafion perfluorinated resin from Shanghai Dibai Biotechnology Co., Ltd., 5% solution, containing 45% water, 48±3% isopropanol, <4% ethanol) was added, and ultrasonic dispersion was performed for 30 min to obtain a uniform electrode dispersion. 200 uL of the above electrode dispersion was dropped on a 0.5×1 cm 2 The working electrode was prepared by completely drying the carbon paper (HCP020P, from HESEN) at room temperature.

[0037] Example 9 Accurately weigh 5 mg of the catalyst Cu synthesized in Example 5, disperse it in 480 uL of volatile solvent isopropanol, then add 20 uL of Nafion solution (Nafion perfluorinated resin from Shanghai Dibai Biotechnology Co., Ltd., 5% solution, containing 45% water, 48±3% isopropanol, <4% ethanol), and ultrasonically disperse for 30 min to obtain a uniform electrode dispersion. Take 200 uL of the above electrode dispersion and drop it on a 0.5×1 cm 2 The working electrode was prepared by completely drying the carbon paper (HCP020P, from HESEN) at room temperature.

[0038] Example 10 Accurately weigh 5 mg of the catalyst In synthesized in Example 6, disperse it in 480 uL of the volatile solvent isopropanol, then add 20 uL of Nafion solution (Nafion perfluorinated resin from Shanghai Dibai Biotechnology Co., Ltd., 5% solution, containing 45% water, 48±3% isopropanol, <4% ethanol), and ultrasonically disperse for 30 min to obtain a uniform electrode dispersion. Take 200 uL of the above electrode dispersion and drop it on a 0.5×1 cm 2 The working electrode was prepared by completely drying the carbon paper (HCP020P, from HESEN) at room temperature.

[0039] Application test In a three-electrode system of an H-type electrolytic cell filled with a 0.5 M KHCO3 aqueous solution, the electrodes prepared in Example 7, Example 8, Example 9 and Example 10 were used as working electrodes, a saturated calomel electrode (SCCE) was used as a reference electrode, and a platinum mesh electrode was used as a counter electrode (the working electrode and the reference electrode were at one end, and the counter electrode was at the other end) to perform constant voltage electrolysis, and magnetic stirring was applied at a stirring speed of 500 rpm min -1 , the constant voltage electrolysis voltage range is -0.5 V to -0.9 V. The selectivity of the catalysts prepared in Example 2, Example 3, Example 4, Example 5 and Example 6 for catalytic reduction of CO2 to synthesis gas was tested.

[0040] Figure 2 The TEM (ab), HRTEM (cd) of the catalysts prepared in Example 2 (Cu4In1 / BP-56) and Example 3 (Cu4In1) of the present invention and the EDS Mapping (e) of the catalyst prepared in Example 2 (Cu4In1 / BP-56) are given. Figure 2 a and Figure 2 As can be seen from Figure b, both Cu4In1 / BP-56 and Cu4In1 catalysts exist in the form of small particle agglomerates. Comparison of the two figures shows that the addition of BP does not affect the morphology of Cu4In1. Figure 2 c and Figure 2 d It can be seen that the Cu and In in Cu4In1 / BP-56 and Cu4In1 exist in the form of Cu2O and In(OH)3 respectively, and the composition of Cu and In will not change before and after adding BP. Figure 2 e shows that in the Cu4In1 / BP-56 sample, Cu, In, O and P elements are evenly distributed in the sample, proving the successful addition of BP and the successful synthesis of the Cu4In1 / BP-56 catalyst.

[0041] Figure 3 The XRD patterns (a) of the catalysts prepared in Example 2 (Cu4In1 / BP-56) and Example 3 (Cu4In1) of the present invention and the XPS patterns (bf) of the catalyst prepared in Example 2 (Cu4In1 / BP-56) are given. The XRD pattern of the Cu4In1 / BP-56 sample shows obvious Cu2O peaks (~32.5°, ~42.4° and ~61.6°) and In(OH)3 peaks (~22.3°, ~31.7°, ~51.2° and ~56.5°), which are consistent with the above HRTEM results. In addition, the Cu4In1 / BP-56 sample also shows peaks corresponding to Cu3P (~39.1° and ~49.1°), which also indicates that BP is successfully added and combines with Cu to form Cu phosphide. XPS full spectrum ( Figure 3 b) and the corresponding fine spectrum also prove that Cu is mainly in the form of Cu + In exists in the form of In 3+ In addition, the appearance of P-Cu bonds in the P 2p fine spectrum indicates the formation of Cu phosphide, which confirms the XRD results.

[0042] Figure 4 The present invention provides Example 3 (Cu4In1), Example 4 (Cu n XPS patterns of the catalysts prepared in Example 1 (In1), Example 5 (Cu) and Example 6 (In). Figure 4 a is the Cu 2p XPS fine spectrum, Figure 4 b is the In 3d XPS fine spectrum. From the figure, we can see that Cu n The valence state of Cu in In1 is basically the same as that in Cu4In1 / BP-56, while the In element in the In sample contains not only In 3+ , there is also elemental In.

[0043] Combination Figure 2 , Figure 3 and Figure 4It can be seen that the Cu element in Example 2, Example 3, Example 4 and Example 5 basically exists in the form of Cu2O, the In element in Example 2, Example 3 and Example 4 exists in the form of In(OH)3, and the In element in Example 6 not only exists in the form of In(OH)3 but also contains part of the In element. The In element is not conducive to the electrocatalytic reduction of CO2 to produce CO, and the composite of Cu2O and In(OH)3 can generate CuIn alloy in situ during the reaction process, and the presence of CuIn alloy can promote the production of CO from CO2. In addition, in the XRD and XPS diagrams of Example 2, the presence of Cu3P phase is also found. Cu3P can effectively produce H2 in the CO2 electrocatalytic reduction aqueous solution, and then produce synthesis gas. Therefore, the content of BP in the catalyst can be controlled to control the content of Cu3P, so as to achieve the purpose of regulating the ratio of H2 / CO in the synthesis gas.

[0044] Figure 5 The present invention provides Example 3 (Cu4In1), Example 4 (Cu n Figure 1 shows the Faraday efficiency of the catalysts prepared in Example 1 (Cu) and Example 5 (Cu) for the catalytic reduction of carbon dioxide. The Faraday efficiency (FE) was evaluated by constant potential measurement to quantitatively compare the activity of the various example catalysts for producing synthesis gas. Figure 5 As shown, after adding In to Cu, FE CO The FE of Cu4In1 at each potential is significantly increased and reaches a peak value when the Cu:In ratio is 4:1. CO The results show that the catalyst prepared in Example 4, especially Cu4In1, has strong selectivity for CO production.

[0045] In addition to effectively catalyzing CO2 reduction, controlling the H2 / CO ratio is also crucial for practical applications. Figure 6 The Faraday efficiency and current density of CO2 reduction to produce synthesis gas at a potential of -0.6 V for Cu4In1 / BP-m prepared in Example 1 of the present invention with different BP contents (150 ~ 700 μg) are given. It can be found in the figure that as the BP content gradually increases, the H2 production capacity gradually increases and the CO production effect is suppressed ( Figure 6 a). At the same time, there is a quasi-linear relationship between the BP content and the molar ratio of H2 / CO in the synthesis gas ( Figure 6 b). This result shows that syngas with any H2 / CO ratio can be obtained simply by changing the BP content in the catalyst.

[0046] Figure 7The Faraday efficiency and current density diagrams (a, c) of the catalyst (Cu4In1 / BP-m) prepared in Example 1 of the present invention, i.e., the CO2 reduction to produce synthesis gas at -0.5 V vs. RHE and -0.9 V vs. RHE at different BP contents (150 ~ 700 μg), as well as the linear fitting curves (b, d) of the BP content and the H2 / CO ratio in the synthesis gas are given. The results show that: at other applied potentials, there is still a linear relationship between the BP content and the H2 / CO ratio, indicating the wide applicability of the synthetic catalyst of the embodiment of the present invention.

[0047] Figure 8 The validation test of the catalyst (Cu4In1 / BP-m) obtained in Example 1 of the present invention by inverting the BP content through the linear fitting curve is given. According to the linear formula, at a potential of -0.6 V vs. RHE, the H2 / CO ratio is 1:2, corresponding to a BP content of 0.25% (a); the H2 / CO ratio is 1:1, corresponding to a BP content of 0.38% (b); and the H2 / CO ratio is 2:1, corresponding to a BP content of 0.63% (c). Based on the inversion results, catalysts Cu4In1 / BP-25, Cu4In1 / BP-38 and Cu4In1 / BP-63 were synthesized and verified 5 times respectively. The verification results show that catalysts Cu4In1 / BP-25, Cu4In1 / BP-38 and Cu4In1 / BP-63 can produce synthesis gas with H2 / CO ratios of 1:2.0, 1.1:1 and 1.7:1, respectively. It is basically consistent with the set results. It shows the accuracy of the fitted linear relationship.

[0048] In practical applications, the stability of catalysts is crucial. Fig. 9 The present invention provides a constant potential electrolysis of the prepared catalyst Cu4In1 / BP-63 for 18 h at a potential of -0.6 V vs. RHE, and the current density does not decrease significantly. More importantly, the ratio of H2 / CO is always maintained at around 2.0:1, which is suitable for the production of diesel ( Fig. 9 ), which indicates that the catalyst has high stability.

[0049] Fig.10 This is the XPS graph of the catalyst Cu4In1 / BP-63 (corresponding to a H2 / CO ratio of 2:1) prepared in the present invention, in which the XPS characterizations before and after the CO2 electrocatalytic reduction reaction were tested (ac). The XPS comparison before and after the reaction shows that the Cu 2p spectrum + Peak and In 3d spectrum 3+ The peak value decreased significantly, indicating that as the CO2 reduction reaction proceeded, Cu + andIn 3+The in-situ generation of CuIn alloy promoted the generation of CO, and in the P 2p spectrum, the P-Cu bond peak value was enhanced, indicating an increase in Cu3P products. This result shows that the CuIn alloy generated by the CuIn / BP catalyst during the CO2 reduction reaction is the key to the efficient production of CO by the catalyst, and the increase in Cu3P content can promote the production of H2. The combined effect of the two further regulates the H2 / CO ratio in the synthesis gas.

[0050] In summary: The present invention simply and easily prepares the CuIn / BP catalyst by one-step NaBH4 co-reduction of the Cu precursor, In precursor and BP single substance, and has excellent catalytic effect. Synthesis gas with different H2 / CO ratios can be obtained only by changing the BP content in the catalyst, and the catalytic stability is good. It has the potential to be applied to industrial production and has good application prospects.

[0051] The above are only preferred embodiments of the present invention, but the present invention is not limited to the above specific implementation schemes. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a CuIn / BP catalyst for electrocatalytic CO2 reduction to produce syngas with precise and controllable ratio, characterized in that: The steps include: 1) exfoliating black phosphorus crystals to form black phosphorus monolayer nanosheets; dispersing the black phosphorus monolayer nanosheets in DMF to form a precursor solution A; 2) Dispersing metal copper salt and metal indium salt in deionized water to form precursor solution B; 3) Disperse NaBH4 in deionized water to form solution C; 4) After mixing precursor solution A and precursor solution B, add solution C and separate the solid and liquid to obtain.

2. The method for preparing the CuIn / BP catalyst according to claim 1, characterized in that: In step 1), a black phosphorus crystal is exfoliated in a N,N-dimethylformamide solution containing tetrabutylammonium hexafluorophosphate using a direct current power supply to apply a voltage to form a black phosphorus monolayer nanosheet, and the applied voltage is -10 to -14 V.

3. The method for preparing the CuIn / BP catalyst according to claim 1, characterized in that: In step 1), 2 g of black phosphorus crystals are added to 30-50 mL of N,N-dimethylformamide solution containing 1-3 g of tetrabutylammonium hexafluorophosphate.

4. The method for preparing the CuIn / BP catalyst according to claim 1, characterized in that: In step 2), the metal copper salt is copper nitrate trihydrate, and the metal indium salt is indium nitrate hydrate; the molar ratio of the metal copper salt to the metal indium salt is 3-5:

1.

5. The method for preparing the CuIn / BP catalyst according to claim 1, characterized in that: The molar ratio of the black phosphorus monolayer nanosheet, the sum of the molar amounts of the metal copper salt and the metal indium salt, and NaBH4 is 0.001-0.1:2:

3.

6. The CuIn / BP catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the CuIn / BP catalyst described in claim 6 in electrocatalytic CO2 reduction to produce synthesis gas with precise and controllable proportions.

8. The use according to claim 7, characterized in that: The CuIn / BP catalyst is dispersed in a volatile solvent, and a Nafion solution is added as a binder to uniformly disperse the mixture to obtain a uniform electrode dispersion; the electrode dispersion is coated on carbon paper and dried at room temperature to obtain a working electrode; and constant voltage electrolysis is performed in a closed three-electrode system.

9. The use according to claim 8, characterized in that: The volatile solvent is isopropanol; the volume ratio of the volatile solvent to the Nafion solution is 22-26:1, and the mass concentration of the Nafion solution is 4-6%; in the electrode dispersion, the concentration of the CuIn / BP catalyst is 8-12 mg mL -1 .

10. The use according to claim 8, characterized in that: The three-electrode system uses a saturated calomel electrode as the reference electrode and a platinum mesh electrode as the counter electrode. Constant-potential electrolysis is performed in a 0.5 M KHCO3 aqueous solution. The voltage used for constant-potential electrolysis is -0.5V ~ -0.9V.

Citation Information

Cited By

  • Integrated system for preparing methanol through electro-catalysis-thermocatalysis coupled with optical energy storage and CO2 capture

    CN122032447A